Relationship Between Nurses' Knowledge and Implementation of Decubitus Assessment Reassessment at Hospital X - Linda Muria Sari; Enna Rossalina Sihombing (Arbain Publishing, 2025)
Pressure ulcers occur due to reduced blood supply and tissue malnutrition caused by continuous pressure on the skin. The incidence of pressure ulcers continues to rise. The prevalence of pressure ulcers remains very high worldwide, with 2.5 million people in the United States, 1.67% in Asia, 50% in Australia, 49% in Europe, 5%-32% in Canada and the UK, and 29% in Jordan. Therefore, an accurate assessment is required. Pressure ulcer assessment using the Braden scale is crucial. Braden scale assessment should be conducted daily, referred to as reassessment, to help prevent the occurrence of pressure ulcers. The aim of this study is to identify the relationship between nurses' knowledge and the implementation of pressure ulcer assessments at Hospital X in 5 inpatient wards and the ICU. The research method involves using the Braden scale as a measurement tool. The study was conducted at Hospital X. The study population includes all nurses in the inpatient wards and the ICU. Using Slovin's formula, 65 respondents were selected. This study employs frequency distribution tests for univariate analysis and Kendall's tau b test for bivariate analysis. The study was carried out from November 2023 to January 2024. Univariate research results: Characteristics of the respondents include those aged 26-35 years (55.4%), female gender (63.1%), Bachelor's degree (53.8%), working experience of 5-10 years (64.6%), sufficient knowledge (39 individuals, 60.0%), and performing pressure ulcer assessments (36 individuals, 55.4%). The bivariate research results showed that there is a significant relationship between nurses' knowledge and the implementation of reassessment for pressure ulcer assessments at Hospital X (p value 0.000). A relationship was found between nurses' knowledge and the implementation of reassessment for pressure ulcer assessments at Hospital X (p value 0.000). It is recommended that nurses improve patient care, especially for patients at risk of developing pressure ulcers, by minimizing the risk of pressure ulcer formation through periodic patient repositioning or mobilization.